Edgar Allan Poe : rhetoric and style - Zimmerman, Brett, 1958- (McGill-Queen's University Press, 2005)
"Poe may have left a significant legacy in American literature, transforming the short story and developing the genres of psychological thriller and detective story, but his prose has often come under attack as unreadable and has led to a volatile debate over his style. Through an examination of several of Poe's most important tales and a catalogue of literary and rhetorical terms illustrated with examples, Brett Zimmerman evaluates the author's technical artistry and convincingly defends him a an apt stylist"--Provided by publisher